THE PROBLEMS OF CRIMINAL RESPONSIBILITY OF LEGAL ENTITIES: FOREIGN EXPERIENCE - Гаврилішин, Анатолій Петрович; Козирєва, Валентина Петрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2018)
Purpose: in the article the questions of theoretical and practical application of criminal responsibility are examined in relation to legal entities taking into account experience of criminal legislation of peoples Republic of China. Methods: used methods of analysis, comparison and synthesis. Results: the ways of perfection of national criminal legislation are offered taking into account foreign experience. Discussion: problems of criminal legislation of Ukraine and requirement in his perfection.